Digital Literacy in the Early Childhood Islamic Education Space in Purwokerto - Wulandari, Suci; Trisnawati, Asysyifa Dian (Annual Conference on Islamic Early Childhood Education (ACIECE), 2024)
The Society 5.0 era is a civilization where digital technology is a solution to solve various problems as well as a tool to improve the social welfare of the community. The presence of this civilization is marked by rapid technological advances and disruptions in various spaces including the education space, especially early childhood Islamic education. Based on this, digital literacy is an important aspect that must be introduced to early childhood in carrying out its role as a digital generation. This research was conducted with the aim of exploring digital literacy in the early childhood Islamic education space, focusing on the opportunities and challenges faced. This research is a qualitative research with a case study method on 3 early childhood Islamic education institutions in the city of Purwokerto (RA Rumah Kreatif Wadas Kelir, RA Muslimat NU Masyithoh 13 Sokaraja, and TK Diponegoro 173 Teluk, Purwokerto) with data collection through interviews with educators, parents, classroom observations, and curriculum documentation. The results of the study show that digital literacy has a great opportunity to improve the quality of early childhood learning and introduce the wise use of technology, including: 1) Children who are Adaptive and Flexible to Technology; 2) Ability to Absorb Information Quickly; 3) Children's Tendency to Think Logically, Analytically, And Openly. However, behind the opportunity, there are also challenges of digital literacy in the early childhood Islamic education space, namely: 1) Information Overload; 2) Digital Distraction; 3) Moral Degradation